The JPS Bible Commentary: Psalms 120-150 (Book collections on Project MUSE., 2023)
"This volume of the Jewish Publication Society's highly acclaimed Bible Commentary series provides the Hebrew text of Psalms 120-150 along with the JPS English translation and a line-by-line commentary"--